?STUDIES ON MIXED LIGAND COMPLEXES OF IRON (III), CHROMIUM (III) AND NICKEL (II) CONTAINING DICARBOXYLIC ACID AND 5, 7, 7, 12, 14, 14 HEXAMETHYL 1, 4, 8, 11 TETRAAZACYCLOTETRADECA 4, 11 DIENE (Biological Sciences - PJSIR, 1998)
Mixed ligand complexes of Fcflfl), Cr(TII) and Ni(ll) with dicarboxylic acid and 14 membered tctraazarnacrocyclcs have been synthesized. The general composition of the complexes are trans-lM(DAL]n+ where n=o, I and DA = dibasic acids c.g. Hornophthalic acid (I-1m), Diphcnic acid (Dp) and L = 5,7,7.14,14-hcxarncthyl-l ,4,8,II-tetl'aazacyclotctradeca-4, l l-dicnc. These complexes were characterized on the basis or elemental analyses, conductomctric, magnetic, infrared, column and thin layer chromatography and electronic spectral tudies. The present complexes are high spin species consistent with essentially octahedral stcrcochemisty with trans configuration.